Correlation of susceptibility to ortho-aminoazotolueneinduced hepatocarcinogenesis with Car and Ahr signaling pathway activation in mice - N. V. Baginskaya; E. V. Kashina; M. Yu. Shamanina; S. I. Ilnitskaya; V. I. Kaledin; V. A. Mordvinov (Вавиловский журнал генетики и селекции)
Ortho-aminoazotoluene (OAT) is a potent hepatocarcinogen for most strains of mice. It has previously been shown that OAT application activates the aryl hydrocarbon receptor (Ahr) and the constitutive androstane receptor (Car) in the mouse liver. Both of these receptors are directly involved in the process of hepatocarcinogenesis. In this study, we investigated the effect of chronic OAT administration on the mRNA expression levels of Ahr, Car and their target genes Cyp1a1 and Cyp2b10 in the liver of DD/He (DD) and CC57BR/Mv (BR) mouse strains contrasting in sensitivity to hepatocarcinogenesis. The inflammatory response of these strains was also studied. Male mice of both strains received OAT oil solution at the dose of 225 mg/kg body weight four times within two months. Control animals received the equivalent solvent amount. Mice were sacrificed on days 1 and 4 after the last OAT administration. Gene expression levels in the liver were determined by real-time PCR. The inflammatory response was evaluated by serum concentration of tumor necrosis factor alpha (TNF-alpha). In resistant BR mice, OAT induced a pronounced and prolonged increase in Cyp1a1 mRNA, showing primarily Ahr activation, while the DD strain displayed a more pronounced elevation of Cyp2b10 expression, indicative of Car activation. In addition, a strong inflammatory response to OAT was recorded in DD mice but not in BR. It is assumed that the prevalence of Ahr signaling pathway activation over Car signaling pathway activation is a factor of resistance to OAT-induced hepatocarcinogenesis.